BUILDING TEAM EFFECTIVENESS THROUGH WORK ATTACHMENT TRAINING - Tri Luckhi Yudha Atmaja; Sus Budiharto (RADJA PUBLIKA, 2026)
The effectiveness of the team is one of the important factors that determines the success of an organization in achieving its goals. This study aims to test the effect of work attachment training on increasing team effectiveness in employees of human resources consulting companies in Yogyakarta. The study used a quasi-experimental design of a pretest-posttest control group involving 24 participants, consisting of 12 people in the experimental group and 12 people in the control group. Data were collected using the Team Effectiveness Scale and the Work Engagement Scale. Data analysis was carried out using the Mann–Whitney and Wilcoxon tests. The results of the study show that work attachment training is effective in increasing team effectiveness. Gain score analysis showed significant differences between the experimental group and the control group (W = 107.00; p = 0.045; d = 0.486). In addition, the experimental group experienced a significant increase in team effectiveness after training (W = 1.50; p = 0.006) as well as an increase in work attachment (W = 13.00; p = 0.045). These findings suggest that work attachment training can be one of the human resource development strategies to increase the effectiveness of teams in organizations.